Smart Contract Technology for Blockchain-based Systems: Design and Implementation Challenges. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
The technology of smart contracts, which is an essential component of blockchain-based systems, has the potential to improve the efficiency, transparency, and safety of these systems. However, there are a number of challenges that need to be conquered in order to develop and implement smart contracts, particularly in regard to security, adaptability, interoperability, and meeting the standards imposed by legal and regulatory authorities. This paper examines ideas for designing and implementing smart contracts, as well as providing an outline of the challenges that have been encountered. In this article, we take a look back at 25 essential works that were published in the field between 2010 and 2019, and we discuss the impact that these works have had. According to the findings of our research, continual collaboration between the necessary stakeholders is required in order to fully realize the benefits given by smart contract technology while also limiting the risks associated with it.